(untitled) (Studia Prawnicze / The Legal Studies, 1965)
The introduction contains technical, organizational and economic considerations which justify the introduction into the Construction Contractor Agreement according to the resolutions on the general provisions of the Contractor Agreements for Construction and Installation Works (Monitor Polski, 1958, No. 32, art. 186). At the same time, there is an opinion that the general contractor — subcontractor relationship may not apply to further links, that, in its turn, the subcontractor cannot engage the third parties to perform part or all of the work entrusted to them. These introductory remarks conclude with a discussion of the possibilities for maintaining the subcontractor institution against the backdrop of the relevant provisions of the new Civil Code. The second chapter describes “the subject matter, obligations under the Subcontractor Agreement, the goals and content of this Agreement”. The direct goal is to achieve the direct economic result of the subcontractor work, while the indirect goal is to achieve the final economic result from the entire range of work performed by the general contractor together with all subcontractors. Thus, the purpose of the Agreement is clearly defined here. If the purpose of the Agreement is in conflict with the current regulations, then this is the basis for rescission of the Agreement. The meaning of the Subcontractor Agreement is to determine the method that leads the parties to the achievement of the Agreement purpose and, in particular, to the establishment of the rights and obligations of the parties, the subject and execution period. If the subject-matter of the Agreement is inconsistent with the provisions of the law in force while the Agreement purpose corresponds to the plan, it is necessary to find a way to correct the subject-matter. The third chapter entitled “Conclusion of a Subcontractor Agreement” considers issues related to the choice of a counterparty,* discusses the need for the principle of zoning and the role of the administrative decisions in the work distribution. Searching for a legal structure of the available obligations of an enterprise received the so-called “preliminary task” leads to the conclusion that this is not any kind of a civil law relationship structure but an obligation under administrative law arising from the current regulations. The next chapter “Contractual relationship between the subcontractor and the general contractor and relationship between the subcontractor and the investor” initially provides a systematisation of the relations uniting three parties bound by two agreements (subcontractor — general contractor and general contractor — investor), and then considers the rights and obligations of the general contractor as an intermediate link between the investor and the subcontractor, as well as the rights and obligations that directly bind the investor and the subcontractor. The role of the investor’s supervision for the subcontractor is covered in detail: the investor is an actual owner who oversees the investment task implementation during the entire period of work. Based on the scope of the investor’s powers, we can see that they usually assign management functions to the general contractor but can take over the execution of these functions at any time — as opposed to a traditional contractor agreement under which the customer has sole control over the task executor. The fact of this structure inclusion under Art. 485 of the previous Code of Obligations into the provisions of the Civil Code relating to the Construction Agreement has been met with criticism. When considering the cardinal issue of the subcontractor’s liability (the subcontractor and general contractor bear “joint” liability to the investor), we make reference to the arbitration awards and rulings on disputes for which the issue of liability distribution has been resolved. As for the subcontractor’s responsibility for the defects and shortcomings in the performance of work, they express a reasonable opinion that the subcontractor bears warranty liability for the entire set of works up to the end of the warranty period established by law as well as a view that a contractual penalty may be deducted from the fee due to the subcontractor also when the total amount of fee does not exceed the ceiling amount, if the cost of all the general contracting works exceeds this amount. Among the issues related to the penalty (contractual compensation) for losses, the resolutions on the general provisions of contracts (agreements) regulating the subcontractor’s compensation for losses have been analysed. When considering the acceptance of the works completed, three acceptance functions are distinguished (handover — approbation — performance of the required settings regarding the state of work at the time of acceptance). The indication that the approbation and the documentation are the most important acceptance functions forms the basis for a proper understanding of the regulation on the “simultaneous” investor’s acceptance of the works performed by the general contractor and subcontractor. Searching for a legal structure based on which the subcontractor can require the investor to pay fees for the work completed under the agreement with the general contractor leads to the conclusion that we are dealing with the debt transfer with the creditor’s consent under Art. 519 § 1 and § 2 item 2 of the Civil Code. The fifth chapter describing “the legal structure of the relationship in the triangle: investor — general contractor — subcontractor” states an opinion that the concept of a subcontract in the meaning of the general provisions on agreements does not coincide with the traditional idea of a subcontract as a so-called “business contract”. Hence, they come to a conclusion that the Subcontractor Agreement corresponds to the structure of the contract in favour of the third party in accordance with Art. 393 of the Civil Code. Finally, an attempt to assess the institutions of subcontracting and general contracting for construction and installation works has been made. This assessment is not free of its downsides. Admission of the principles of “joint” responsibility, “simultaneous” work acceptance and direct payments to the subcontractor by the investor entails a serious demobilization of the general contractor in the performance of their duties to control the quality and urgency of work as well as the correctness of payments for them. A special additional chapter is dedicated to issues related to the performance of work by non-socialized subcontractors. The final remarks suggest a separate settlement in future resolutions on the questionable issues related to the Subcontractor Agreement and the publication of the arbitration awards as well as rulings related to the specifics of the Subcontractor Agreement.